Nation Branding: The Case of Indonesia’s Cultural and Tourism Public Diplomacy - Riska Luneto (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
This paper analyzes the implementation of Indonesian tourism nation branding through the wonderful tourism image of Indonesia as a form of state diplomacy. As a soft diplomacy effort by Indonesia, the use of wonderful Indonesia is a manifestation of Indonesia's diversity; culture, tourism, history and other religions. The use of tourism image as public diplomacy is not new in diplomatic studies, departing from traditional diplomacy, modern diplomacy tends to provide benefits for various countries in cooperation efforts. The results found are that the good image of a country can influence the opinion of foreigners towards the country, but the implementation of branding is still a challenge for the country, where the good image has not been able to have a major influence on increasing tourism, where the problem of tourism security tends to be. a big challenge for the country.